2021
DOI: 10.1186/s12955-021-01695-y
|View full text |Cite
|
Sign up to set email alerts
|

Attachment: the mediating role of hope, religiosity, and life satisfaction in older adults

Abstract: Background Attachment and support from family and friends are core to the experiences of ageing for older adults. The purpose of this study is to examine the relationships between attachment styles and hope, religiosity, and life satisfaction and provide new knowledge that may assist future planning for a rapidly ageing global population. Methods In this cross-sectional study, 504 Iranian older adult participants from Qazvin province were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
2
9
0
4
Order By: Relevance
“…The mediating role of personal hope was confirmed at both individual‐level between supportive leadership and personal resilience and cross‐level, between psychosocial safety climate and personal resilience. The results are in line with previous studies which showed the mediating effect of individual strengths such as hope between social supports and human attitudes and behaviours (Pahlevan Sharif et al., 2021; Zhou, et al., 2018). However, this study is the first to investigate and confirm that hope can not only be a key personal resource but can also transmit the effect of organizational resources such as PSC and SL on other crucial resources (in this study PH and PR).…”
Section: Discussionsupporting
confidence: 92%
“…The mediating role of personal hope was confirmed at both individual‐level between supportive leadership and personal resilience and cross‐level, between psychosocial safety climate and personal resilience. The results are in line with previous studies which showed the mediating effect of individual strengths such as hope between social supports and human attitudes and behaviours (Pahlevan Sharif et al., 2021; Zhou, et al., 2018). However, this study is the first to investigate and confirm that hope can not only be a key personal resource but can also transmit the effect of organizational resources such as PSC and SL on other crucial resources (in this study PH and PR).…”
Section: Discussionsupporting
confidence: 92%
“…Duffy et al, 2015;Ginevra et al, 2017b;Di Maggio, et al, 2019). This finding suggests that considering oneself able to construct own future career intentions and to handle career transitions may favor the ability to plan the specific strategies to reach future goals and initiate and sustain the motivation for using those strategies, thus stimulating life satisfaction (Pahlevan Sharif et al, 2021;Scioli et al, 2011;Yaghoobzadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have highlighted that hope is associated with a wide range of indicators of psychosocial well-being, such as fewer behavioral problems, depressive symptoms, and higher levels of personal adaptation, adaptive achievement, and life satisfaction (Gilman et al, 2006;Kenny et al, 2010;Sheldon & Hoon, 2013). Regarding the latter, Yaghoobzadeh et al (2018) found that a person's ability to be hopefulness positively predicts life satisfaction, and more recently, Pahlevan Sharif et al (2021) found that hope, with religiosity, fully mediated the relationship between close attachment and life satisfaction in older adults.…”
Section: Hopementioning
confidence: 99%
“…Some research has focused on other factors where the positive influence of hope has been demonstrated [ 2 , 42 , 43 ], such as spiritual well-being [ 2 ] and sufficient satisfaction of physical and psychological needs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%